2012
DOI: 10.1002/ibd.22865
|View full text |Cite
|
Sign up to set email alerts
|

Role of serum cytokine profile in ulcerative colitis assessment

Abstract: A serum cytokine profile may be an auxiliary tool for the diagnosis and severity assessment of UC. IL-8 seems to be a reliable biomarker, closely related to disease activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 20 publications
2
42
0
Order By: Relevance
“…Unexpectedly, we found an increased production of IL-8 in the CC genotype, which seems to be paradoxical to the results for IL-17, TNFα and IL-1β expression. A similar result was also reported in a study on ulcerative colitis in which the expression of IL-8 was inconsistent with that of IL-17 and IL-1β 36. Collectively, these results suggest that this SNP functionally affects the miR-146a expression level and also influences proinflammatory cytokine production.…”
Section: Discussionsupporting
confidence: 88%
“…Unexpectedly, we found an increased production of IL-8 in the CC genotype, which seems to be paradoxical to the results for IL-17, TNFα and IL-1β expression. A similar result was also reported in a study on ulcerative colitis in which the expression of IL-8 was inconsistent with that of IL-17 and IL-1β 36. Collectively, these results suggest that this SNP functionally affects the miR-146a expression level and also influences proinflammatory cytokine production.…”
Section: Discussionsupporting
confidence: 88%
“…In our patients, IL‐23 and IL‐17 A showed a tendency to increase during the apheresis doses. However, IL‐6 and IL‐8 levels tended to decrease, in line with previously published results that observed that the levels of these cytokines could be good indicators of disease activity . IL‐10 is an anti‐inflammatory cytokine.…”
Section: Discussionmentioning
confidence: 99%
“…However, IL-6 and IL-8 levels tended to decrease, in line with previously published results that observed that the levels of these cytokines could be good indicators of disease activity. 13 IL-10 is an anti-inflammatory cytokine. However, its beneficial effect in IBD is not yet clear, given IL-10 treatment in patients with IBD failed to induce clinical effects.…”
Section: Discussionmentioning
confidence: 99%
“…The small differences in gene expression seen in PBMCs between patients with normal colons and those with endoscopic inflammation is not entirely surprising, given the small differences in gene expression, and levels of cytokines, seen peripherally even in patients with severe clinical and endoscopic colitis (23;24). The differential expression of GATA3 in the PBMCs of patients with endoscopic colitis is consistent with its role as a transcriptional regulator of type-2 helper T-cells (Th2), which are important in the pathogenesis of UC (25-27).…”
Section: Discussionmentioning
confidence: 99%